Public disclosure and tax compliance: evidence from Uganda - Manwaring, P; Regan, T (Centre for the Study of African Economies, 2023)
Public disclosure policies have potential to raise tax compliance where alterna¬tive enforcement capacity is limited. We study the effects of reporting delinquents and recognizing compliers, and provide evidence on the social determinants of tax compliance. Our results are consistent with a model in which being publicly known as tax-eligible is costly but social sanctions for delinquency are limited. Further, disseminating information on tax behavior reduces the compliance of recipients by causing their beliefs to be updated down toward the true compliance rate. Overall, these policies are limited at raising revenue and less effective than simple enforce¬ment reminder nudges.